ABU NASR AL-FARABI’S VIEWS ON MEDICINE - Karomatov Otabek Yunusovich (World Scientific Research Journal, 2025)
Abstract: This article explores the contributions of the great philosopher and scholar Abu Nasr Al-Farabi to the field of medicine. His philosophical approach to health, his insights into the connection between physical and mental well-being, and his emphasis on the moral and preventive aspects of medicine are analyzed. The article also highlights Al-Farabi's influence on later scholars, particularly Avicenna (Ibn Sina), and his role in shaping the foundations of Islamic medical thought.